MdNup54 Interactions With MdHSP70 Involved in Flowering in Apple - Zhang, Chenguang; Zhang, XIaoshuang; Cheng, Bo; Wu, Junkai; Zhang, Libin; Xiao, Xiao; Zhang, Dong; Zhao, Caiping; An, Na; Han, Mingyu; Xing, Libo (Frontiers in Plant Science, 2022)
Flowering-related problems in ‘Fuji’ apple have severely restricted the development of China’s apple industry. Nuclear pore complexes (NPCs) control nucleoplasmic transport and play an important role in the regulation of plant growth and development. However, the effects of NPCs on apple flowering have not been reported. Here, we analysed the expression and function of MdNup54, a component of apple NPC. MdNup54 expression was the highest in flower buds and maintained during 30–70 days after flowering. MdNup54-overexpressing (OE) Arabidopsis lines displayed significantly earlier flowering than that of the wild type. We further confirmed that MdNup54 interacts with MdHSP70, MdMYB11, and MdKNAT4/6. Consistent with these observations, flowering time of MdHSP70-OE Arabidopsis lines was also significantly earlier. Therefore, our findings suggest a possible interaction of MdNup54 with MdHSP70 to mediate its nuclear and cytoplasmic transport and to regulate apple flowering. The results enhance the understanding of the flowering mechanism in apple and propose a novel strategy to study nucleoporins.